DAMPAK PAJAK EKSPOR CPO TERHADAP BEBERAPA ASPEK INDUSTRI CPO INDONESIA: SIMULASI MODEL EKONOMETRIK (IMPACTS OF CPO-EXPORT TAX ON SEVERAL ASPECTS OF INDONESIAN CPO INDUSTRY: SIMULATION OF ECONOMETRIC MODEL) - WAYAN R. SUSILA; IDM. DARMA SETIAWAN (Program Studi Agribisnis, Fakultas Pertanian, Universitas Udayana Jalan PB.Sudirman Denpasar, Bali, Indonesia. Telp: (0361) 223544 Email: soca@unud.ac.id, 2001)
To control domestic supply and price of crude palm oil (CPO) and cooking oil, thegovernment of Indonesia has imposed CPO-export tax since August 1994. As the CPO industry playsan important role in Indonesian economy, the imposition of the tax has perceived to have substantialimpacts on various aspects of the industry, such as on investment, production, trade, farm income, andwelfare distribution. In line of this issue, the main objective of this study is to assess these impactsusing an econometric model of the industry.The results of the study reveal that this export tax policy has inhibited the growth rate ofinvestment, production, export, and farm income. On the other hand, this policy has been an effectiveinstrument to control domestic CPO and cocking oil price. Moreover, this policy has caused asubstantial welfare transfer from producers to consumers and the government. To compromise theseconflicting impacts, an alternative CPO tax formula is also proposed within this paper.